What Stresses Mothers Most in the Neonatal Unit? Environmental and Infant-Illness Stressor Profile among Mothers of Neonates with Sepsis at Kenyatta National Hospital - Adelight Nabwire; Morris Senghor Shisanya (East African Journal of Health and Science, 2026)
Background: Mothers of neonates admitted with sepsis remain in the neonatal unit in a demanding environment while their infant is critically ill. Identifying which specific stressors mothers find most burdensome is essential for targeting family-centred support, yet stressor profiling is rarely reported from sub-Saharan African neonatal units. This study characterised the perceived stressfulness of environmental and infant-illness factors among mothers at Kenyatta National Hospital (KNH) and examined whether stressor burden tracks global perceived stress. Methods: In a cross-sectional study, 70 of 78 eligible mothers (response rate 89.7%) rated 19 stressor items on a five-point scale (1 = not stressful to 5 = extremely stressful), grouped a priori into three domains: infant illness (6 items), the unit environment (7 items) and worry about the mother’s own situation (6 items). Domain scores (item means), internal consistency (Cronbach’s alpha), item rankings with 95% confidence intervals (CIs), paired Wilcoxon domain comparisons (Holm-adjusted) and Spearman correlations with the 10-item Perceived Stress Scale (PSS-10) were computed in R (version 4.1.2). Results: All three domains were internally consistent (alpha 0.73–0.78). Infant-illness stressors were rated most stressful (domain mean 3.29), significantly higher than environmental (2.53; Holm p < 0.001, rank-biserial r = 0.64) and sociodemographic-worry stressors (2.24; p < 0.001, r = 0.73). The single most stressful items were the baby being unable to breastfeed (mean 3.64; 68.6% very/extremely stressful), the baby being on oxygen (3.44; 64.3%), sick babies sharing cots (3.44; 60.0%) and separation from the baby (3.39). Notably, none of the domain scores was significantly correlated with global perceived stress (all p ≥ 0.101; combined model R² = 0.05). Conclusion: Mothers’ stress in the neonatal unit is driven chiefly by their infant’s illness and by concrete, modifiable care circumstances—separation, inability to breastfeed and cot-sharing—rather than by ambient ward conditions. Because stressor exposure did not predict global perceived stress, situational stressor checklists and appraisal-based scales capture different constructs and should be used together. Interventions that shorten separation, support expressed-milk feeding and relieve cot-sharing are the most direct levers for reducing maternal stress.